Meminimalisasikan Resiko Dalam Transaksi Melalui Legal Due Diligence - Iskandar, Yosea (LAW REVIEW, 2001)
In 1999, Equalnet Communication and e. Volve planned a merger worth between $70 and $ 80 million. The merger seemed to be a natural fit. e. Volve was a facilities-based company , while Equalnet provided long distances communication service; e. Volve focused on wholesale international business .while Equalnet focused on retail domestic business. However, two month after its due diligence review ofe. Volve, it called off the merger. What deal-breaker had due diligence uncovered ? Equalnet learned that e. Volve only had two large customers, and its only current international business Â between the United States and Mexico. Although Equalnet already know that e. Volve was only in the planning stages for providing telecommunications services in more countries, Equalnet had been given the impression that these plans were more advanced than they were. Also, Equalnet learned that e. Vollves relationships with its present customer weren t as solid as had been represented. Both corporation went their separate ways and on to different projects and partnership. Due diligence showed that Â this match could have been a costly mistake. Due diligence (Blacks Law dictionary) is such a measure of prudence activity or assiduity, as is properly to be expected from and ordinarily exercised by a reasonable and prudent man under the particular circumstances ; not measured by any absolute standard but depending on the relative facts of the special case. Counsel who conduit due diligence reviews as part of the prospective merger or acquisition know that no one analytical method can be used for every acquisition. There are some tools, however that can be modified and used often. One such tool is a list of subjects in which representatives of the selling company can be questioned to test the health and the risk of their business. Another tool is the representations and warranties that the seller can be asked to make in the documents that tire exchanged at settlement. A third is a method of review that tries to merge a financial analysis of the sellers business with an analysis of the business.Â